Development of a learning module on environmental pollution based on the local realities of Pedamaran subdistrict for tenth grader - Nyayu Annisa Gustanti; Nike Anggraini; Rahmi Susanti (Universitas Muhammadiyah Malang, 2025)
Environmental pollution learning in high schools does not sufficiently link the material to the local environmental realities of students in Pedamaran subdistrict. This study aims to develop a local reality–based environmental pollution teaching module for senior high school students in Pedamaran subdistrict and to determine its feasibility for classroom use. This study employed a Research and Development (R&D) using the ADDIE model, the population included Grade X students of SMAN 1 Pedamaran, with a sample of 10 students selected through purposive sampling. Data were collected through expert validation sheets, student response questionnaires, and classroom observation instruments. Quantitative descriptive analysis using Likert and Guttman scales was applied to convert qualitative assessments into percentage scores. The results show that the developed module uses clear language, relevant illustrations, and interactive content grounded in local environmental issues. Validation by material and media experts produced an average feasibility score of 87%. Classroom implementation received a score of 96.4%, and student responses reached 100%. These findings indicate that the local reality based environmental pollution module is highly feasible and appropriate for supporting Biology instruction and fostering students’ environmental literacy at the senior high school level.